Grain refinement in an unalloyed tantalum structure by combining Wire+Arc additive manufacturing and vertical cold rolling - Marinelli, Gianrocco; Martina, Filomeno; Ganguly, Supriyo; Williams, Stewart W. (Elsevier, 2019)
Components manufactured via Wire + Arc Additive Manufacturing are usually characterised by large columnar grains. This can be mitigated by introducing in-process cold rolling; in fact, the associated local plastic deformation leads to a reduction of distortion and residual stresses, and to microstructural refinement. In this research, inter-pass rolling was applied with a load of 50 kN to a tantalum linear structure to assess rolling’s effectiveness in changing the grain structure from columnar to equiaxed, as well as in refining the grain size. An average grain size of 650 μm has been obtained after five cycles of inter-pass rolling and deposition. When the deformed layer was reheated during the subsequent deposition, recrystallisation occurred, leading to the growth of new strain-free equiaxed grains. The depth of the refined region has been characterised and correlated to the hardness profile developed after rolling. Furthermore, a random texture was formed after rolling, which should contribute to obtaining isotropic mechanical properties. Wire + Arc Additive Manufacture demonstrated the ability to deposit sound refractory metal components and the possibility to improve the microstructure when coupled with cold inter-pass rolling.
Keywords: WAAM; Tantalum; Microstructure; Hardness; Cold working; Additive manufacturing